The Strengths and Weaknesses of Deliberation on River Basin Management Planning: Analysing the water framework directive implementation in Catalonia (Spain). (2nd March 2015) - Parés, Marc; Brugué, Quim; Espluga, Josep; Miralles, Júlia; Ballester, Alba
Abstract By the means of evaluating the planning process carried out in Catalonia (Spain) according to the requirements of the implementation of the EU Water Framework Directive, this article explores the relation between the characteristics of a deliberative process and its results. Our research examines the effects of a real deliberative process on river basin management planning, identifies its strengths and weakness and unveils those factors that explain the lights and the shadows of deliberation. Our evaluation shows that, although the deliberative process achieved significant outputs, most of the participants were unsatisfied with the results. The article concludes that the behaviour rules of the participants, the methodology used, the political engagement and the resources invested are crucial to understanding most of the deliberative processes' success. On the other hand, the lack of deliberative culture, the existence of weak governmental leadership and the absence of some key actors explain the participants' dissatisfaction with the results. Copyright © 2015 John Wiley & Sons, Ltd and ERP Environment